Manajemen pembelajaran guru ditinjau dari motivasi kerja, kompetensi dan budaya sekolah di Ibu Pawiyatan Tamansiswa Yogyakarta tahun ajaran 2013/2014 - Paulus Parsego; Mundilarno Mundilarno (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
This study is aimed to determine: 1) motivation, competence, and school culture together against learning management teacher, 2) the effect of work motivation on teacher learning management, 3) the effect of teacher competence on learning management, and 4) the effect of school culture on teacher learning log management on teachers in the Capital Pawiyatan Tamansiswa Yogyakarta. This study is a survey that uses a quantitative approach. The populations of study were 108 teachers in Ibu Pawiyatan Tamansiswa Yogyakarta spread across 5 schools. This study was a population. The data collection technique used is questionnaires. The validity of the test of one by study Cronbach alpha product Moment correlation, reliability test questionnaire using Cronbach Alpha. Correlative analysis of the data using multiple regression analysis with three predictors F test and partial correlation. The results showed that the variables of work motivation, competence and school culture simultaneously significant effect on the learning management teacher at Ibu Pawiyatan Tamansiswa Yogyakarta. Variable work motivation is the partially significant effect on teacher learning management. Variable competence partially significant effect on teacher learning management. The magnitude of the effective contribution of the three variables, namely the variables of work motivation, competence, and school culture affect the learning management teacher at Ibu Pawiyatan Tamansiswa Yogyakarta. Based on the value of the effective contribution of the independent variables indicate the dominant variables that influence learning management work motivation of teachers is variable.